Model Pengelolaan Kepiting Bakau untuk Kelestarian Habitat Mangrove di Taman Nasional Kutai Provinsi Kalimantan Timur - Wijaya, Nirmalasari Idha; Yulianda, Fredinan (Bumi Lestari; Vol 19 No 1 (2019)DO - 10.24843/blje.2019.v19.i01.p01, 2019)
The National Park Kutai (TNK) has ± 5.227 ha mangrove forest in along coastal beach.  Therefore , almost 23% of mangrove forest was degraded effect to land conversion and utilization of damaged. Mud crab (Scylla serrata) is one of the resources in mangrove ecosystem, thus can be utilized for the cultivation sylvofishery. The Utilization was an alternative livelihood for the local resident in TNK areas that was not damaged their forest necessity. The model of sylvofishery utilization mud crab prepared were 5 sub-models, such as  mangrove habitat sub-model, catching Mud Crab sub-model, enlargement cultivation of mud crab sub-model, market sub-model, social sub-model. The simulation results of the dynamic model, was showed optimistic of scenario performance model to sustainable for management of mangrove forest in The TNK thus conducted with optimization approached resources in utilization of Scylla serrata. With silvofishery expected balance between utilization and conservation of mangrove ecosystems.